beta-Endorphin: formation of alpha-helix in lipid solutions. - Wu, C S (Proc Natl Acad Sci U S A, 1979)
Human beta-endorphin adopts a partial helical conformation in aqueous solutions of cerebroside sulfate, ganglioside GM1, phosphatidylserine, and phosphatidic acid, but not of cerebroside and phosphatidylcholine, as evidenced by circular dichroic spectra. Addition of Ca2+ to the peptide in cerebroside sulfate solution can break up the helix; at 10 mM Ca2+ the peptide (12 microM) essentially exists in an unordered form. For comparison, sheep beta-lipotropin in acidic cerebroside sulfate solution (pH less than 4) also has a partial helical conformation of the complex between human beta-endorphin and lipids may be related to the opiatelike function of this peptide hormone.